Charcoal from coffee husks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The Kenya Planters Cooperative Union (KPCU), an organisation of coffee growers, has set up a factory which is now producing 200 tonnes of charcoal a month from 400 tonnes of coffee husks. The technique might result in saving trees from being used...